ARDUINO-BASED FALL DETECTION AND ALERT SYSTEM - Mohd Arifin, Izuan Alif (Universiti Teknologi PETRONAS, 2017)
Over decades, accident fall is believed to be the major cause of deaths and cause serious injuries to the elders. As their health performances turns down, they tend to have joint pains, cognitive problems and as well as the brain problems. They sometimes need support to keep standing and worse case, they need a caregiver. However, the cost of having a caregiver may burden the relatives. The caregiver also could not all the time that keep an eye on the elders and they might fall when they are alone. There are many devices that have been developed in order to cope with this problem. Some uses webcam and some uses pendant. However, there are drawbacks of using these approaches. In this project, a smart Arduino-based fall detection and alert system is developed to monitor elder activities and alert the respective person if there is any accident fall. Accelerometer and gyro sensor is used to tell the Arduino any changes in the elder’s activity that exceeds the threshold that has been set. This project developed a robust algorithm with a sensitive and an accurate result for fall detection device by more than 90%.